A to Z of earth scientists - Gates, Alexander E., 1957- (New York : Facts on File, 2003)
Alphabetically arranged entries profile more than 150 male and female scientists from the eighteenth century to the present who have made significant contributions to a particular scientific discipline.
Includes bibliographical references (p. 322-324) and index.
Choice.
Wilson's Senior High School.
Young Adult
Keywords: Earth scientists -- Biography -- Dictionaries; Earth scientists -- Biography -- Dictionaries